2020
DOI: 10.3390/molecules25133051
|View full text |Cite
|
Sign up to set email alerts
|

Complete Microbial Fuel Cell Fabrication Using Additive Layer Manufacturing

Abstract: Improving the efficiency of microbial fuel cell (MFC) technology by enhancing the system performance and reducing the production cost is essential for commercialisation. In this study, building an additive manufacturing (AM)-built MFC comprising all 3D printed components such as anode, cathode and chassis was attempted for the first time. 3D printed base structures were made of low-cost, biodegradable polylactic acid (PLA) filaments. For both anode and cathode, two surface modification methods using ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, there still is scope for improvement; several studies have come up with cheap and commonly available materials that can be used to make separator membranes in microbial fuel cells. Khalili et al [204] explored the use of unglazed wall ceramic (UGWC) and unglazed floor ceramic (UGFC) as materials for separating media [205,206]. It was observed that UGFC-based microbial fuel cells produced a maximum power density of 106.89mW m −2 and UGWC-based microbial fuel cells produced a maximum power density of 321mW m −2 .…”
Section: Methodsmentioning
confidence: 99%
“…However, there still is scope for improvement; several studies have come up with cheap and commonly available materials that can be used to make separator membranes in microbial fuel cells. Khalili et al [204] explored the use of unglazed wall ceramic (UGWC) and unglazed floor ceramic (UGFC) as materials for separating media [205,206]. It was observed that UGFC-based microbial fuel cells produced a maximum power density of 106.89mW m −2 and UGWC-based microbial fuel cells produced a maximum power density of 321mW m −2 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite such tremendous potential, studies emphasized the challenges in system design and fabrication, which must be addressed to improve their performance and robustness, especially for scaling-up and commercialization (Dhar et al, 2016b;Sim et al, 2018;Zakaria and Dhar, 2019). Specifically, developing a low-cost and efficient fabrication technique is imperative for advancing METs (Bian et al, 2018a;Theodosiou et al, 2020;You et al, 2020). The utilization of conventional subtractive manufacturing methods is time-consuming and highly laborious and can generate wastes from cutting materials away from larger pieces (Theodosiou et al, 2020;You et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, developing a low-cost and efficient fabrication technique is imperative for advancing METs (Bian et al, 2018a;Theodosiou et al, 2020;You et al, 2020). The utilization of conventional subtractive manufacturing methods is time-consuming and highly laborious and can generate wastes from cutting materials away from larger pieces (Theodosiou et al, 2020;You et al, 2020). Moreover, the precise manufacturing of miniaturized METs for applications like biosensors is also challenging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations